Daily Prayer And Five Times Salat ; A Comparative Study on Christian and Islamic Liturgical Discourse in Indonesia - Hasibuan, Ricky Pramono (AL-ADYAN, 2023)
Daily prayer is one of the oldest ecclesiastical liturgical traditions and has been known since the time of the early church. However, this tradition seems to be fading over time. In Indonesia, daily prayer is no longer widely known by Christians. Meanwhile, the five times salat continue to be practised faithfully by its adherents in the Islamic tradition. Liturgical studies recognize the practice of daily prayer and the five times salat as "canonical hours" or hours of prayer. Although Christians were familiar with the hours of prayer before Islam, Muslims maintain them more faithfully and consistently. This phenomenon will become the focus of this paper in the frame of comparative theology. This paper explores the superior values of the Islamic five times salat, which can be appreciated as inspiration for developing Christian daily prayer.